The challenges of teaching music in a Malaysian secondary school: a case study in SMK Sultan Yahya Petra 1 / Mohd Azrul Hisham Amrah @ Amram - Amrah @ Amram, Mohd Azrul Hisham (2015)
The main aim of this thesis was to find out the challenges faced by Malaysian secondary schools' music teacher. The paperwork includes information of knowledge and skills required by music teachers, Malaysian's perspective towards music, funding, support and perception of music in Islam. This study is performed to find out about school's perception, challenges faced by music teacher and to find solutions for the problem faced by the music teacher in Malaysia secondary school. To achieve this, data has been collected by research from other researchers, books, online journal and interview session by current educators. The paper analyzes the overall factor that happened before, during and future possibilities in Malaysia's secondary school. Through researcher's own experiences during the practical training studies for Bachelor's Degree in UiTM, the researcher faced certain challenges stated in this research. In researcher's own hypothesis, most of students lack of interest in music subject due to social factors, lack of encouragements and support, and lack of exposure. Thus, using all the information received, the researcher will design an interview questions based on the issues related to the topic.